2022
DOI: 10.1177/21925682221085226
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Mitogen-Activated Protein Kinases/Mammalian Target of Rapamycin Pathway in the Process of Cartilage Endplate Stem Cell Degeneration Induced by Tension Load

Abstract: Study Design Basic Research. Objective Intervertebral disc degeneration (IVDD) is caused by the cartilage endplate (CEP). Cartilage endplate stem cell (CESC) is involved in the recovery of CEP degeneration. Tension load (TL) contributes a lot to the initiation and progression of IVDD. This study aims to investigate the regulatory mechanism of the Mitogen-activated protein kinases/Mammalian target of rapamycin (MAPK/mTOR) pathway during TL-induced CESC degeneration. Methods CESCs were isolated from New Zealand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…When JNK was inhibited, the protein levels of the autophagy markers microtubule-associated protein 1 light chain 3 beta-II (LC3-II) and Beclin-1 increased, while the protein levels of p62 decreased. This suggests that the downregulation of JNK may mitigate TL-induced CEP degeneration through the activation of autophagy [26]. Additionally, p38 MAPK is considered to play a crucial role in inhibiting the activation of autophagy.…”
Section: Jnk and P38 Mapk Signaling Pathways Regulate Autophagymentioning
confidence: 97%
See 1 more Smart Citation
“…When JNK was inhibited, the protein levels of the autophagy markers microtubule-associated protein 1 light chain 3 beta-II (LC3-II) and Beclin-1 increased, while the protein levels of p62 decreased. This suggests that the downregulation of JNK may mitigate TL-induced CEP degeneration through the activation of autophagy [26]. Additionally, p38 MAPK is considered to play a crucial role in inhibiting the activation of autophagy.…”
Section: Jnk and P38 Mapk Signaling Pathways Regulate Autophagymentioning
confidence: 97%
“…JNK and p38 MAPK can also increase the content of intracellular reactive oxygen species (ROS), leading to oxidative stress damage, and affect the excessive accumulation of iron in cells, leading to the occurrence of ferroptosis [24,25]. Additionally, inhibition of JNK and p38 MAPK significantly increases the level of intracellular autophagy in NP cells, thus delaying apoptosis and ECM degradation [26,27]. However, the specific signal transduction mechanism of JNK and p38 MAPK in IDD is not clear and needs further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of the JNK signaling pathway alleviates degeneration of stem cells derived from CEP, NP, and bone marrow [ 119 ]. For example, oxidative stress during the transplant of BMSC to degenerative discs may cause cell toxicity and poor survival of BMSCs.…”
Section: Mapk Signaling Pathwaymentioning
confidence: 99%
“…56,59,60,64,66 Eight studies discussed the fate of CESCs in IDD. 54,57,61,63,[68][69][70]76 Eight studies elaborated on the biological potential of CESCs in intervertebral disc regeneration. 55,67,[71][72][73][74][75]77…”
Section: Key Findings Of Cescsmentioning
confidence: 99%
“…These findings provide substantial evidence of CESCs in the CE. Subsequent research has identified CESCs in other species, including rats 70,71,73-75 and rabbits, 76 further broadening the scope of knowledge in this field.…”
mentioning
confidence: 99%